SELLING AND BUYING TRANSACTION MANAGEMENT INFORMATION SYSTEM ANALYSIS : CASE STUDY ONLINE SHOP TATY WHOLESALE IN MAKASSAR - Ibnu Azka; Hadrian Jaya; Fathur Baldan Haramain (Program Studi Manajemen Bisnis Syariah, 2024)
This article aims to analyze the information system in buying and selling practices in case studies at the Taty Grosir online shop in Makassar. In the process of interacting with consumers, professionalism and a good management system are needed so that consumers can experience ease and comfort in transactions. The proliferation of online shops is a challenge for MSMEs to continue to innovate and be creative in making transactions with the support of information technology. The main thing that will be revealed in this research is how good and correct buying and selling transactions are related to Islamic values ??which have so far been neglected in online buying and selling. This research uses field research with qualitative descriptive analysis. Data collection techniques include observation, interviews and documentation. The research results present findings that the buying and selling transaction management information system on the Taty Grosir online shop platform in Makassar is implemented through a series of steps in the buying and selling process, including sales, buyer identification, negotiation, implementation of buying and selling transactions, and delivery of goods. Apart from technical aspects, this research also highlights the values ??of da'wah related to Islamic ethical principles, especially in the context of buying and selling activities. The existence of these values ??is reflected in attitudes and behavior that reflect the characteristics of the Prophet Muhammad, such as Sidiq (honest), amanah (trustworthy), tabligh (convey), and fathanah (intelligent and creative). Thus, this research not only focuses on technological aspects in information systems, but also describes how Islamic moral and ethical principles are reflected in the online buying and selling practices carried out by Taty Grosir in Makassar.